Case Report: Sudden Fatal Hemorrhage in Ulcerative Fungal Laryngotracheitis—A Pediatric Case Report - Porzionato, Andrea; Stocco, Elena; Emmi, Aron; Macchi, Veronica; De Caro, Raffaele (Frontiers in Pediatrics, 2022)
In this report, we describe an autopsy case of a child affected by acute lymphoblastic leukaemia and opportunistic pulmonary aspergillosis. The patient died because of a full-thickness tracheal wall ulceration with right inferior thyroid artery lesion and sudden hemorrhage, likely ascribable to undiagnosed invasive Aspergillus laryngotracheitis. Aspergillus infection, particularly in immunocompromised patients, should be considered an urgent risk factor to manage, as it may lead to sudden fatal events in absence of evident critical symptoms.